2018
DOI: 10.1002/adhm.201800857
|View full text |Cite
|
Sign up to set email alerts
|

Mixed and Matched Metallo‐Nanotexaphyrin for Customizable Biomedical Imaging

Abstract: The discovery and synthesis of multifunctional organic building blocks for nanoparticles have remained challenging. Texaphyrin macrocycles are multifunctional, all-organic compounds that possess versatile metal-chelation capabilities and unique theranostics properties for biomedical applications. Unfortunately, there are significant difficulties associated with the synthesis of texaphyrin-based subunits capable of forming nanoparticles. Herein, the detailed synthesis of a texaphyrin-phospholipid building block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 24 publications
4
17
0
Order By: Relevance
“…In contrast, the porphysome is a recent example of a “one‐for‐all” approach in which the lipid nanoparticle is comprised of a single porphyrin‐lipid building block that when self‐assembled offers a multitude of intrinsic nanoscale functions . Previously developed porphyrin and porphyrin analog‐based lipids such as bacteriochlorophyll‐lipid and texaphyrin‐lipid have shown unique stimuli‐responsive properties and versatile metal‐chelation capabilities, respectively, for cancer imaging. We envision that it is possible for a non‐porphyrin‐based dye‐lipid building block, such as aza‐BODIPY, to assemble into a liposomal structure that introduces novel nanoscale optical properties and broadens the purview of “one‐for‐all” lipid nanoparticles.…”
Section: Figurementioning
confidence: 99%
“…In contrast, the porphysome is a recent example of a “one‐for‐all” approach in which the lipid nanoparticle is comprised of a single porphyrin‐lipid building block that when self‐assembled offers a multitude of intrinsic nanoscale functions . Previously developed porphyrin and porphyrin analog‐based lipids such as bacteriochlorophyll‐lipid and texaphyrin‐lipid have shown unique stimuli‐responsive properties and versatile metal‐chelation capabilities, respectively, for cancer imaging. We envision that it is possible for a non‐porphyrin‐based dye‐lipid building block, such as aza‐BODIPY, to assemble into a liposomal structure that introduces novel nanoscale optical properties and broadens the purview of “one‐for‐all” lipid nanoparticles.…”
Section: Figurementioning
confidence: 99%
“…However, the reason for the strong accumulation observed in the spleen (over 50 times more avidly than the liver on a per gram tissue basis) requires further investigation. Other types of PEGylated nanoparticles have been previously observed to accumulate substantially more in the spleen than liver 44, 45. Of note, Cui and colleagues found that large PEG nanoparticles of both 500 nm and 280 nm accumulated strongly in the spleen, compared to liver.…”
Section: Resultsmentioning
confidence: 98%
“…Porphyrin molecules smartly revitalized the liposomes with excellent therapeutic efficacy and myriad of extensibilities. The porphysome was a fascinating, multifunctional theranostic regime for cancer treatments; Zheng and co-workers have successfully implemented them into various kinds of tumor models for phototherapies (photodynamic and photothermal therapy), ,, NIRFI, , MRI, ,, PAI, ,, SPECT, and PET. ,, …”
Section: Porphyrin-based Liposome (Porphysome)mentioning
confidence: 99%